Ground Hemp Fibers as Filler/Reinforcement for Thermoplastic Biocomposites. (9th June 2015) - Etaati, Amir; Pather, Selvan; Rahman, Moloud; Wang, Hao
Abstract : Mechanical properties (tensile, flexural, and impact) of ground hemp fibre polypropylene composites were investigated. Ground alkali-treated hemp fibre and noil hemp fibres with various initial fibre lengths were utilized to reinforce polypropylene matrix. Firstly, the microstructural and tensile characterizations of the two types of fibres were characterized using scanning electron microscope (SEM), Fourier transform infrared analysis (FTIR), and Dynamic Mechanical Analyser (DMA). Then, the fibres were ground into different lengths of 0.2, 0.5, 1, and 2 mm; composites containing 40 wt% short hemp fibre and 5 wt% maleic anhydride grafted polypropylene (MAPP) were fabricated by means of a twin screw extruder and an injection moulding machine. Finally, influence of hemp fibre type and initial hemp fibre length on tensile property of the composites were investigated. The results revealed that addition of either noil hemp fibre or normal treated hemp fibre into the pure polypropylene matrix increased the tensile strength almost twice and stiffness of the composites more than three times. Although noil hemp fibre composite indicated slightly lower mechanical properties than the normal alkali-treated fibre composites, the difference was not significant. The analysis of the results provided the optimum initial fibre length (powder) of 0.2 mm hemp polypropylene composite. The results can be extended to different types of natural fibres.